2006
DOI: 10.1037/0022-0167.53.3.302
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment, perceived discrimination based on sexual orientation, and depression in gay males: Examining the mediation and moderation effects.

Abstract: This study examined perceived discrimination as both a mediator and moderator between adult attachment (anxiety and avoidance) and levels of depression in a gay male sample. Survey data were collected from 234 self-identified gay males through the Internet and in person through community resources across several states. Results from structural equation modeling analyses indicated that perceived discrimination partially mediated the relationship between attachment anxiety (but not attachment avoidance) and depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 65 publications
3
45
3
Order By: Relevance
“…Evidence of validity is provided by significant correlations in expected directions with other attachment measures and with measures of preferences for touch and sexual behavior (Brennan et al, 1998). Previous studies have used the ECR with LG samples and reported internal reliabilities of .90 for the Avoidance subscale and .94 for the Anxiety subscale (Zakalik & Wei, 2006). Coefficient alphas in the current study were .93 and .92 for the Avoidance and Anxiety subscales, respectively.…”
Section: Instrumentsmentioning
confidence: 70%
“…Evidence of validity is provided by significant correlations in expected directions with other attachment measures and with measures of preferences for touch and sexual behavior (Brennan et al, 1998). Previous studies have used the ECR with LG samples and reported internal reliabilities of .90 for the Avoidance subscale and .94 for the Anxiety subscale (Zakalik & Wei, 2006). Coefficient alphas in the current study were .93 and .92 for the Avoidance and Anxiety subscales, respectively.…”
Section: Instrumentsmentioning
confidence: 70%
“…Other studies using the ECR have also provided support for its validity. For example, attachment anxiety and avoidance have been found to be positively associated with self-concealment and personal problems , ineffective coping (Wei, Heppner, Mallinckrodt, 2003;Wei, Heppner, Russell, & Young, 2006), maladaptive perfectionism Wei et al, 2006), negative mood (Wei, Russell, Mallinckrodt, & Zakalik, 2004), and depression (Zakalik & Wei, 2006) but negatively associated with social self-efficacy and emotional self-awareness and basic psychological need satisfaction (Wei, Shaffer, Young, & Zakalik, 2005) in college student samples. One group of researchers (Fraley, Waller, & Brennan, 2000) suggested additional items that may improve the sensitivity of the ECR across a wider range of adult attachment, but we could not find a single published study that developed a shorter measure based on the ECR.…”
mentioning
confidence: 99%
“…Empirical studies focusing on various components of minority stress in LGB individuals (e.g., experiences of discrimination, anticipation of rejection, and internalized homophobia) have separately documented associations between these factors and negative mental health outcomes, including higher levels of depression, anxiety, and substance use (e.g., Balsam & Mohr, 2007;Huebner, Nemeroff, & Davis, 2005;Szymanski & Owens, 2008;Zakalik & Wei, 2006; also see review in Meyer, 2003). Qualitative studies have documented that marriage amendments (Levitt et al, 2007;Riggle & Rostosky, 2007) and other anti-LGB political campaigns (e.g., Russell, 2000) are perceived as acute prejudicial events by LGB citizens and thus, by definition, are a minority stress factor.…”
mentioning
confidence: 99%